Insights into alpha-defensin modulation of non-enveloped viral infection - Hu, Ciara Tipping (My University, 2023)
Alpha-defensins are small antimicrobial peptides that play a crucial role in innate immunity across various mammalian species. Possessing broad antimicrobial properties, they have neutralizing activity against bacteria and both enveloped and non-enveloped viruses. These peptides are either constitutively secreted into the intestinal lumen (enteric) or stored inside granules in neutrophils which subsequently fuse to pathogen-carrying vesicles (myeloid). Despite the presence of defensins, some pathogens can resist their antimicrobial effects or even exploit these antimicrobial peptides to enhance their infection. Given the observed trend of many enteric pathogens being resistant to or enhanced by enteric alpha-defensins, we hypothesized that alpha-defensins can assert selective pressure on pathogens. To investigate this hypothesis, I focused on two non-enveloped viruses: adenovirus and rotavirus. Prior studies on adenoviruses identified the vertex proteins, fiber and penton base, as being important determinants of defensin antiviral activity. Using a directed evolution approach, a different major capsid protein, hexon, was identified as being an additional determinant of defensin activity and a driver of defensin-mediated enhancement. My infection and biochemical assays suggest that a balance between increased cell binding and a downstream block in intracellular trafficking mediated by defensin interactions with all the major capsid proteins dictates the outcome of infection. Investigation into defensins’ effects and mechanisms of action on rotavirus are in their infancy. We examined how defensins impact the infection of various rotavirus strains, and we observed that rotaviruses were resistant to or enhanced by their host’s enteric defensins. We also interrogated the potential role of myeloid and non-host alpha-defensins as cross-species barriers and found that the outcome varied depending on the specific rotavirus strain tested. To elucidate the proteins involved, we used reassortant viruses, and identified the rotaviral spike protein, VP4, as a determinant for defensin-mediated modulation of rotavirus infection. Subsequently, I investigated if using a directed evolution approach, similar to that employed with adenovirus, would provide greater insight into defensins’ ability to drive viral evolution. Moreover, I sought to identify specific regions of the rotavirus virion that are targeted by defensin. I found that rotavirus was able to evolve resistance to a previously neutralizing myeloid defensin and that most of those mutations were in the spike protein. This reinforces the significance of VP4 in determining defensins’ effect on rotavirus. Interestingly, despite the emergence of defensin resistance mutations in the receptor binding pocket, I found that defensin does not inhibit rotavirus binding to cells. Future investigations into entry and trafficking may reveal that rotavirus neutralization by defensins follows a similar overarching mechanism observed for other non-enveloped viruses. This mechanism involves α-defensins disrupting proper trafficking of the virus by altering capsid dynamics.
Thesis (Ph.D.)--University of Washington, 2023
Keywords: Adenovirus; Alpha-defensin; Defensin; Evolution; Non-enveloped virus; Rotavirus; Microbiology; Virology; Immunology; Microbiology